Association of hospital volume and long-term survival after esophagectomy: A systematic review and meta-analysis - Wang, Qing; Mine, Shinji; Nasu, Motomi; Fukunaga, Tetsu; Nojiri, Shuko; Zhang, Chun-Dong (Frontiers in Surgery, 2023)
Background It remains controversial whether esophageal cancer patients may benefit from esophagectomy in specialized high-volume hospitals. Here, the effect of hospital volume on overall survival (OS) of esophageal cancer patients post esophagectomy was assessed. Methods PubMed, Embase, and Cochrane Library were systematically searched for relevant published articles between January 1990 and May 2022. The primary outcome was OS after esophagectomy in high- vs. low-volume hospitals. Random effect models were applied for all meta-analyses. Subgroup analysis were performed based on volume grouping, sample size, study country, year of publication, follow-up or study quality. Sensitivity analyses were conducted using the leave-one-out method. The Newcastle-Ottawa Scale was used to assess the study quality. This study followed the Preferred Reporting Items for Systematic Reviews and Meta-analysis guidance, and was registered (identifier: INPLASY202270023). Results A total of twenty-four studies with 113,014 patients were finally included in the meta-analysis. A significant improvement in OS after esophagectomy was observed in high-volume hospitals as compared to that in their low-volume counterparts (HR: 0.77; 95% CI: 0.71–0.84, P < 0.01). Next, we conducted subgroup analysis based on volume grouping category, consistent results were found that high-volume hospitals significantly improved OS after esophagectomy than their low-volume counterparts. Subgroup analysis and sensitivity analyses further confirmed that all the results were robust. Conclusions Esophageal cancer should be centralized in high-volume hospitals.